2020
DOI: 10.1002/jtr.2395
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the coronavirus pandemic on Europe's tourism industry: Addressing tourism enterprises and workers in the undeclared economy

Abstract: The coronavirus pandemic has led to revenue loss for tourism enterprises and workers due to restrictions on movement. In response, governments have made available temporary financial support, but not to those tourist enterprises and workers in the undeclared economy. Reporting a 2019 Eurobarometer survey, this paper reveals that one in 165 European citizens engage in undeclared work in tourism and the groups involved. To bring these enterprises and workers onto the radar of the state, a voluntary disclosure in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 31 publications
(27 reference statements)
1
73
0
10
Order By: Relevance
“…The right to travel and enjoy hospitality facilities has been restricted in way which was unprecedented since the world wars [6]. This situation has led to enormous revenue loss for tourism enterprises due to restrictions on movement [7], amplified by high uncertainty related to global travel restrictions [8]. The coronavirus outbreak also alters images of particular destinations, and may harm especially those suffering from high infection rates, while in contrast, can be beneficial for some other destinations [1].…”
Section: Introductionmentioning
confidence: 99%
“…The right to travel and enjoy hospitality facilities has been restricted in way which was unprecedented since the world wars [6]. This situation has led to enormous revenue loss for tourism enterprises due to restrictions on movement [7], amplified by high uncertainty related to global travel restrictions [8]. The coronavirus outbreak also alters images of particular destinations, and may harm especially those suffering from high infection rates, while in contrast, can be beneficial for some other destinations [1].…”
Section: Introductionmentioning
confidence: 99%
“…Insurance and subsidy programs for employees; support the survival of the hotel and airline industry [3,[13][14][15][16][17] Play the function of the informal sector Cooperation between the informal sector and government departments; provide microfinance; provide bank insurance [18,19] Prioritize actions Quick response to the tourism industry in crisis [13,15] Formulate public policy Prohibit or restrict the arrival of giant cruise ships and promote the development of small cruise ships; issue policies to support the aviation and hotel industry; government supervision of policy implementation [12,20,21] Table 5. Government crisis management: after the crisis.…”
Section: Financial Supportmentioning
confidence: 99%
“…However, government support currently depends on voluntary disclosure by companies. Williams [14] found that even if the government provides short-term financial support to the affected workers and enterprises, this can only offset the loss of income declared by the enterprises, employees, and self-employed individuals. Businesses, employees, and self-employed individuals in the undeclared economy will not receive this support.…”
Section: Conduct Recovery Marketingmentioning
confidence: 99%
“…Moreover, Government restrictions had an effect in businesses downturns and changes in consumer behaviour (Sheth, 2020). This new reality brought also opportunities for some business, as for example, a significantly strengthened of the online sales channels (Williams, 2020;Hao et al, 2020). However, in general, the economic activity has been disrupted.…”
Section: Introductionmentioning
confidence: 99%